2013
DOI: 10.1177/0146167213484769
|View full text |Cite
|
Sign up to set email alerts
|

“I Guess What He Said Wasn’t That Bad”

Abstract: Although confrontations can be an effective means of reducing prejudicial responding, individuals often do not confront others due to the interpersonal costs. In the present research, we examined the intrapersonal implications of not confronting prejudice. In three studies, female participants were exposed to a confederate who made a sexist remark. Consistent with self-justification theories, in Study 1, participants who valued confronting and were given the opportunity to confront-but did not-subsequently mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…Also, non-confrontation may leave members of stigmatized groups feeling inauthentic, feeling they failed to be loyal to their true selves and personal goals. Such dissonance has been found to be so aversive that people who do not confront sometimes minimize the seriousness of the bias claim to restore a positive sense-of-self (Rasinski et al, 2013).…”
Section: Potential Hidden Costs Of Dealing With Stigmamentioning
confidence: 99%
“…Also, non-confrontation may leave members of stigmatized groups feeling inauthentic, feeling they failed to be loyal to their true selves and personal goals. Such dissonance has been found to be so aversive that people who do not confront sometimes minimize the seriousness of the bias claim to restore a positive sense-of-self (Rasinski et al, 2013).…”
Section: Potential Hidden Costs Of Dealing With Stigmamentioning
confidence: 99%
“…There is very little work on the effects of not confronting so we had to estimate parameters based on evidence from one study in the context of gender bias and two studies in the context of racial bias. Rasinski, Geers, & Czopp (2013) found that among individuals who said that confronting sexism was important to them, not confronting a sexist comment (relative to being exposed to a sexist comment without the opportunity to confront) decreased self-reported importance of confronting on a second measure. Specifically, not confronting decreased participants' beliefs in the importance of confronting from 6.7 to 5.9 (estimated from figure): a difference of 0.8 on a 7-point scale.…”
Section: Does Bias Confrontation Change Subsequent Likelihood Of Bias?mentioning
confidence: 93%
“…Negative reactions could be even more likely on the part of dominant group members when the ostracism is perpetrated by ingroup members against a member of an ethnic minority group because of the social identity threat represented by the possibility that their ingroupand by extension they themselves-are racist or appear to be racist [47][48][49]. Consistent with this idea, witnessing but not confronting discriminatory behavior has been shown to be a potentially dissonance-arousing experience [50]. Further, prior research suggests that the salience of a dominant group identity may elicit a variety of negative group-based emotions if individuals appraise their ingroup as responsible for perpetrating harm or illegitimate advantage over an outgroup [51,52].…”
Section: Enhanced Reactivity Hypothesismentioning
confidence: 94%